Melestarikan Kearifan Lokal: Revitalisasi Randai dan Tari Tradisional serta Dukungan terhadap Tradisi Manjapuik Anak di Nagari Sibakur - Ali Basrah Pulungan; Zahratul Khairia; Indah Intania Permata; Inda Lestari; Rinda Gusnawati; Ella Anggraini (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study aims to examine efforts to preserve local wisdom in Nagari Sibakur, Tanjung Gadang District, Sijunjung Regency, through the revitalization of traditional performing arts such as Randai and traditional dance, and the strengthening of the cultural tradition of manjapuik anak (children’s dance) in wedding ceremonies. The importance of this topic lies in concerns about the fading of local cultural identity due to modernization. This research was conducted through direct observation by 29 students during their Community Service Program (KKN) in Nagari Sibakur, using a descriptive qualitative approach along with observation, interviews, and documentation techniques with artists, traditional leaders, and the local community. The results indicate that the existence of Randai and traditional dance is still actively maintained through training for the younger generation and traditional activities. The tradition of manjapuik anak also continues to be practiced as an important part of the Minangkabau social structure. This preservation has received strong support from the community and the village government. This research confirms that preserving local wisdom not only preserves cultural heritage but also strengthens the identity and sense of community togetherness.